Verbal and Nonverbal Sexual Harassment in Catcalling Cases - Fetri Reni; Zumiarti Zumiarti; Rahmad Surya; Shally Amna (The Future of Education Journal, 2026)
This study examines the phenomenon of catcalling as a form of verbal and nonverbal sexual harassment experienced by women in public spaces. Although catcalling is often perceived as a joke, compliment, or harmless behavior, it can evoke feelings of discomfort, fear, anger, embarrassment, and insecurity among victims. This study aims to explore women's understanding of catcalling, identify the forms of catcalling occurring in Pariaman, and analyze the factors contributing to its occurrence. A qualitative approach was employed using purposive sampling, with data collected through in-depth interviews, observations, documentation, and a literature review. The findings reveal that while some participants were familiar with the term catcalling, not all recognized it as a form of sexual harassment. The identified forms of catcalling included whistling, winking, suggestive gestures, flirtatious remarks, comments on women's bodies, and intrusive staring that caused discomfort. Catcalling commonly occurred in public places such as markets, streets, and workplaces. The findings further indicate that catcalling is closely associated with patriarchal culture, the objectification of women's bodies, and the widespread misconception that such behavior is merely playful or harmless. This study contributes to a deeper understanding of gender-based harassment in public spaces and highlights the need for greater public awareness and preventive measures to protect women's safety and dignity.